Sleep disorders and COVID-19 - Bhat, Sushanth; Chokroverty, Sudhansu (Sleep medicine, 2022)
This chapter summarizes the known associations between COVID-19 and sleep dysfunction, including insomnia, excessive daytime sleepiness, restless legs syndrome and nightmares, and touches upon pandemic-related considerations for obstructive sleep apnea and continuous positive airway pressure treatment. Treatment strategies and management approaches are also briefly discussed.